STRATEGI PENGEMBANGAN PARIWISATA BERBASIS MASYARAKAT PADA DESA WISATA NYAMBU - I Ketut Muliarta (Universitas Triatma Mulya, 2021)
The purpose of holding this research is to find out the tourism potential of Nyambu tourism village, and how this community-based tourism development is carried out in Nyambu tourism village, to obtain suitable strategies to be applied in the future. Based on the results of the analysis, it can be concluded that Nyambu tourism village has a variety of tourism potentials both natural, cultural and artificial which are also supported by large potential human resources in terms of quantity and quality but have not been optimally involved in tourism development. From the results of the SWOT analysis, it can be determined that the main strategy (Grand Strategy) in community-based tourism development in the tourist village of Nyambu is increasing awareness and community participation in tourism activities. This community participation is in the form of participating in promoting the existence of the tourist village of Nyambu through information technology. Supporting alternative strategies consist of: cooperation with travel agents, promotion, utilization of village funds, product diversification, environmental preservation, mentoring, foreign language training and community innovation.